Characteristics of Orange-Footed Scrubfowl (Megapodius reinwoardt) Nests in Kerandangan Natural Tourism Park West Lombok - Putri, Hestiani; Yamin, M.; Hadiprayitno, Gito (Jurnal Biologi Tropis, 2024)
Orange-footed scrubfowl (Megapodius reidwardt) are protected species and need to be preserved. Orange-footed scrubfowl (Megapodius reidwardt) are terrestrial birds that build nests on the ground. To maintain its sustainability, it is necessary to have knowledge about the characteristics of orange-footed scrubfowl nests. Kerandangan Natural Tourism Park is one of the places where orange-footed scrubfowl are found, but until now there is still no information about the characteristics of orange-footed scrubfowl nests. So this study aims to analyze the characteristics of orange-footed scrubfowl nests in Kerandangan Natural Tourism Park. The method used in this research is descriptive exploration, the research variables include physical parameters of the nest, environmental parameters of the nest, chemical parameters of the nest mound and plant vegetation around the nest. The results showed that the diameter of the nest ranged from 400-590 cm with a nest height of 85-154 cm, the number of laying holes ranged from 1-3 holes and the soil texture class of the nest mound consisted of sandy loam and loam. Environmental parameters obtained average temperature outside the nest 27,9oC, average temperature inside the nest 28,6oC, average humidity outside the nest 80,3%, humidity inside the nest 81,2% and light intensity ranged from 98,1-834,1 lux in the morning, 437,8-4014,8 lux in the afternoon, and 45,7-653,8 lux in the afternoon. Chemical parameters obtained organic matter content ranged from 1,4%-3,2% and pH ranged from 6,8-7. Vegetation that had the highest INP in each nest was Voacanga foetida, Inga edulis, Artocarpus elasticus, and Bambusa bambos, these plant species act as materials for building nest mounds and potentially as food for orange-footed scrubfowl.